Feeding Intolerance and Gastric Acid Levels of the Neonates (Annals of Medical Research, 2021)
Aim: The aim of this study is to investigate the relationship between feeding intolerance, a common problem at neonatal intensive care units, and gastric pH levels. The gastric fluid pH levels of the preterm and term infants with feeding intolerance has been measured and compared with those of a control group.
Keywords: s: Newborn; Feeding Intolerance; Gastric Ph.